Prevalence and Causes of Sick Leave among Healthcare System Employees of Joibar Province in 2015 - Siavosh Etemadi neZhad; Fereshteh Rostami; Jamshid Yazdani charati; Fatemeh Soghra Yousufi golafshani (Mazandaran University of Medical Sciences, 2017)
Introduction and purpose: Absenteeism is defined as being absent from work without a good reason. Sick leave among healthcare providers can have serious negative impacts on organizational performance. This study was conducted to determine the prevalence and causes of sick leave in the healthcare system of Joibar, Iran. Methods: This analytical cross-sectional study was performed on all employees of the healthcare system of Joibar, Iran (n=239). Data was collected using a checklist including demographic data and reasons for absenteeism (the number of absent days, work experience, and  employment status) by presenting to the Human Resources Department of the healthcare system. Data was analyzed by using Chi-square test and Spearman’s rank correlation coefficient in SPSS, version 20. Results: The mean age of the employees was 35.72±3.3 years. Sick leave was mostly observed in the age group of 30-39, official staff, married women, and employees with work experience of 6 to 10 years (83 cases). Among the studied diseases, cold and musculoskeletal disorders were the most frequent causes of absenteeism among employees in the healthcare system. Conclusion: Based on our findings, musculoskeletal disorders were the most important causes of absenteeism, which are preventable. To improve the physical and ergonomic conditions of the staff, we suggest healthcare authorities to install ergonomy software (Office Exercise Program) and provide standard and adjustable seats and office desks.